Repeated cycles of chemical and physical disinfection and their influence on Mycobacterium avium subsp. paratuberculosis viability measured by propidium monoazide F57 quantitative real time PCR - Kralik, Petr; Babak, Vladimir; Dziedzinska, Radka (Veterinary journal (London, England, 2014)
Mycobacterium avium subsp. paratuberculosis (MAP) has a high degree of resistance to chemical and physical procedures frequently used for the elimination of other bacteria. Recently, a method for the determination of viability by exposure of MAP to propidium monoazide (PMA) and subsequent real time quantitative PCR (qPCR) was established and found to be comparable with culture. The aim of this study was to apply the PMA qPCR method to determine the impact of increasing concentration or time and repeated cycles of the application of selected disinfectants on MAP viability. Different MAP isolates responded to the same type of stress in different ways. The laboratory strain CAPM 6381 had the highest tolerance, while the 8819 low-passage field isolate was the most sensitive. Ultraviolet exposure caused only a partial reduction in MAP viability; all MAP isolates were relatively resistant to chlorine. Only the application of peracetic acid led to the total elimination of MAP. Repeated application of the treatments resulted in more significant decreases in MAP viability compared to single increases in the concentration or time of exposure to the disinfectant.
Keywords: Chlorine; Propidium monoazide quantitative PCR; dezinficiencia; Viability; mikrobiální viabilita; kyselina peroctová; azidy; Disinfection; Mycobacterium avium subsp. paratuberculosis; Microbial Viability; ultrafialové záření; bakteriální proteiny; chlor; Propidium; Disinfectants; propidium; Bacterial Proteins; Real-Time Polymerase Chain Reaction; Ultraviolet Rays; Peracetic Acid; kvantitativní polymerázová řetězová reakce; Azides